Ireland : Extended Arrangement-Interim Review Under the Emergency Financing Mechanism. (IMF Staff Country Reports; Country Report ;, 2011)
The Executive Board approved a three-year Extended Arrangement under the Extended Fund Facility (EFF) for Ireland under the exceptional access policy and Emergency Financing Mechanism (EFM). Political developments have been turbulent. The authorities are moving ahead with a comprehensive strategy to restore confidence in the banking sector. The program objectives for the financial sector, while simple and straightforward, require complex strategies for implementation. Efforts are under way to address data gaps and further strengthen data quality. Robust procedures for program monitoring have been established.